Association Between Microalbuminuria and Demographic Profile with Diabetes Mellitus in Children and Adolescents (Mediscope, 2025)
Introduction: Diabetic nephropathy is the leading cause of morbidity and mortality in diabetes mellitus. Microalbuminuria is the first clinical sign of nephropathy.Methods: This was a cross-sectional study conducted on 512 children and adolescents with diabetes mellitus (DM) attending CDiC Clinic in BIRDEM-2 hospital over a one-year period, to determine the association of microalbuminuria with demographic variables. Clinical data were recorded including age of onset of diabetes, age at registration, duration of diabetes, hypertension and family history. Then the results were compared between patients without microalbuminuria and those with microalbuminuria.Results: In this study, we observed that the prevalence of microalbuminuria was 88.7% and normoalbuminuria was 7.7% in children and adolescents with diabetes mellitus. The study also revealed a higher mean age at diagnosis in microalbuminuria compared to normoalbuminuria (15.6 ± 2.2 vs 16.2 ± 2.2) which was statistically significant. The participants also had a higher mean at visit, shorter duration of diabetes in microalbuminuric subjects compared with normoalbuminuric subjects which was statistically significant (p